Dying for Attention: The Role of the Biafran Identity in the Biafran Campaign for Support during the Nigerian Civil War of 1967-70 - Willms, Joshua P. (Université d'Ottawa / University of Ottawa, 2011)
This study examines the Biafran secession of 1967-1970 and how the secessionist government constructed a Biafran identity in its campaign to gain international support for Biafra’s permanent separation from Nigeria. The introductory chapter outlines the role of identity in Nigeria’s twentieth-century political history and discusses the scholarly literature addressing questions of national and ethnic identity and on the Biafran secession. The thesis then provides a historical framework for discussing the evolution of Nigerian political identities and the failures of Nigerian leaders to build a Nigerian nationalism among the region’s numerous identifiable groups in the colonial and early independence eras. Subsequent chapters analyse the Biafran government’s attempts to elide the inherent instability of identity and overcome the dynamic process of identity formation in Nigeria by constructing and promoting a fixed Biafran identity based on cultural characteristics and historical experiences that allegedly distinguished and united the diverse peoples of the secessionist region.
Keywords: Africa; Biafra; civil war; ethnicity; Ibo; identity; modernity; modernization; nation; Nigeria; Ojukwu; secession